Danish but not Lutheran : the impact of Mormonism on Danish cultural identity, 1850-1920 - Allen, Julie K. (The University of Utah Press, 2017)
"This book concerns the introduction of Mormonism to Denmark, which led to an influx of Danish converts into Mormon and Utah society, but it is less about that immigrant infusion than about the impact of Mormonism on Denmark, which turns out to have been profound, not so much because of the alien LDS religion as because of the nature of Danish society. Mormon missionaries arrived in Denmark shortly after the establishment of religious freedom in a uniformly Lutheran nation. That helped engender a long, continuing process of renegotiating a Danish national identity distinct from Lutheranism. Mormon proselytizing and the thousands of Danes who converted to the LDS religion were a spur to thinking about national identity and a foil for many of the commentators, among whom two of the most prominent were the estranged brothers Kierkegaard--Søren and the Reverend Doctor Peter Christian--each of whom used discussion of Mormonism in their divergent arguments about Danish Lutheranism. Theirs was part of an extensive high-culture discourse, but Danish popular culture also had much to say about Mormons, in various media from nineteenth-century street ballads to early twentieth-century silent films. Julie K. Allen sees these particular historical matters as means to broach larger questions of the roles of religion and identity in a culture, particularly a relatively homogeneous one such as Denmark's"--Provided by publisher